Effects Of Social Media On Self-Confidence Of Millennials - Aliasger Wagh (International Journal of Advanced Science and Technology, 2020)
Self Confidence is a feeling of trust in one’s abilities, qualities, and judgement. The research was conducted to understand the effects of social media use on millennials self-confidence. The study explored the social media usage patterns by millennials and statistically analysed the effects of social media on self-confidence levels by applying descriptive and inferential statistics. A structured questionnaire was developed by analysing the related literature and reliability test testifies that the data collection instrument was stable enough to measure the phenomenon. Data collected from a sample of 65 respondents. The findings of the study revealed the negative effects of social media on confidence levels of millennials. However, there were a few cases wherein the individuals had a positive influence because of the use of social media. There was a significant difference of opinion among males and females opinion in terms of certain effects. These differences also varied in different age groups of a different gender. The study mentioned that Facebook, WhatsApp, Instagram, and YouTube were used daily by the students. Most of the students were using social media technologies through cell phone. The study has theoretical implications for researchers and practical implications for parents, guardians, peers, caretaker and higher education institutions.